Variación estacional del viento en Costa Rica y su relación con los regímenes de lluvia - Muñoz Moya, Ana Cecilia (2002)
The monthly wind distributions of 22 stations located in different regions of Costa Rica are analyzed. It is found that these distributions respond to the wind behavior at the synoptic scale and its interaction with topography. The stations which show the greater wind speeds are identified, as well as the range of variation of the wind speed and the predominant wind direction through the year. This analysis indicates that the stations located at barlovent, with respect to wind direction, have lower speeds than the ones located at sotavent. The station La Tejona, located near Arenal reservoir, shows the maximum values, reaching a speed of 37.1 km/h in February. The stations located in the Central Valley also show relatively high wind speeds. In the majority of the analyzed stations, the predominant wind direction corresponds to the Trade winds. The influence of the sea breeze (mesoscale wind) and the equatorial westerlies (synoptic scale wind) is observed at the stations of Puntarenas, Damas, Pindeco and Palmar Sur. The rainfall distributions at the same 22 stations, used for the wind distributions, are also analyzed with the purpose to establish if exist any relationship among these variables. The results show differences between the Pacific Watershed and the Caribbean Watershed. The majority of the analyzed stations in the Pacific Watershed show an opposite behavior between wind and rainfall. This clearly establish the influence of the Trade winds intensity in the production of rainfall and identify, in this region, a dry season and a rainy season. This behavior is not observed in the Caribbean Watershed